Fatigue performance of high strength steel built-up box t-joints - Chiew, Sing Ping (2015)
In this study, experiments were conducted to study the fatigue behaviors of two full scale high strength steel built-up box T-joints. Firstly, the stress concentration factors at the joint intersection were measured. Secondly, fatigue tests were conducted with the crack growth monitored by the Alternating Current Potential Drop micro-gauge. It is found that the fatigue resistance of the high strength steel joints could be conservatively predicted by the existing fatigue design curves for normal strength steels. In addition, the higher residual stress present in the joints seems to produce little effects on the crack penetration rate in the thickness direction.